Applying phase equilibria modelling to igneous systems by coupling trace element partitioning and accessory phase saturation to compositionally variable thermodynamic modelling in Rcrust - Hoffman, Sean (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.